Genetic Response of Common Bean to the Inoculation with Indigenous Fusarium Isolates - Alejandra J. Porteous-Álvarez (Journal of Fungi, 2020)
Fungal species from the genus Fusarium are important soil-borne pathogens worldwide, causing significant economic losses in diverse crops. The need to find sustainable solutions against this disease has led to the development of new strategies—for instance, the use of biocontrol agents. In this regard, non-pathogenic Fusarium isolates have demonstrated their ability to help other plants withstand subsequent pathogen attacks. In the present work, several Fusarium isolates were evaluated in climatic chambers to identify those presenting low or non-pathogenic behavior. The inoculation with a low-pathogenic isolate of the fungus did not affect the development of the plant, contrary to the results observed in plants inoculated with pathogenic isolates. The expression of defense-related genes was evaluated and compared between plants inoculated with pathogenic and low-pathogenic Fusarium isolates. Low-pathogenic isolates caused a general downregulation of several plant defense-related genes, while pathogenic ones produced an upregulation of these genes. This kind of response to low-pathogenic fungal isolates has been already described for other plant species and fungal pathogens, being related to enhanced tolerance to later pathogen attacks. The results here presented suggest that low-pathogenic F. oxysporum and F. solani isolates may have potential biocontrol activity against bean pathogens via induced and systemic responses in the plant.